Dopisy Maxmiliána Hillebrandta hraběti Vratislavovi z Mitrovic z obsazené Prahy roku 1742 - Radmila Pavlíčková; Pavel Prchal (Theatrum Historiae)
The study emerges from an analysis of 40 letters sent by Maxmilian Hillebrandt (?-1757) in the first half of the year 1742 to Franz Karl Count Wratislaw of Mitrowitz (1679-1750). At that time, Hillebrandt worked as his house tutor and regularly wrote to the Count, who was active in the Saxon-Polish court in Dresden, giving extensive accounts from Prague, which was occupied by French and Bavarian units. The aim of the study is to describe the spectrum of themes that Hillebrandt referred to, and subsequently to analyse the limits and possibilities of the information he possessed as well as his own reactions to the limits of his reports. In Hillebrandt’s reports there most often appear these thematic spheres, where their order corresponds with the space that he himself reserved for them: 1. Reporting concerning the situation in the city. 2. Provincial military events. 3. European military events. 4. The financial and economic situation of the Count’s domains, often accompanied by reports by aristocratic representatives in the form of appendices. 5. Information from society, especially from the circle of rulers and news about the Prussian king, or about Karl Albrecht. 6. European political events. 7. The topical deaths of socially important people.